A geophysical investigation of the 2018 Lake Muir earthquake sequence: reactivated Precambrian structures controlling modern seismicity. Issue 5 (4th July 2021) - Standen, S.; Dentith, M.; Clark, D.
Abstract: Seismicity in the intraplate southwest of Western Australia is poorly understood, despite evidence for potentially damaging earthquakes of magnitude > M6. Identifying stress-focusing geological structures near significant earthquake sequences assists in understanding why these earthquakes occur in seemingly random locations across a region of more than 250 000 km 2 . On 16 September 2018, an ML 5.7 earthquake occurred near Lake Muir in the southwest of Western Australia and was followed by an ML 5.4 aftershock. The main earthquake formed a mainly north-trending fault scarp ∼5 km in length and with a maximum vertical displacement of ∼40 cm. The main event was followed by a series of aftershocks, one of which had a magnitude of ML 5.4. Using high-resolution aeromagnetic data, we analyse bedrock geology in a wide area surrounding the new scarp and map a series of major ∼ east–west-trending faults segmenting eight distinct geological domains, as well as a network of less prominent northwest-trending faults, one of which aligns with the southern segment of the scarp. Surface faulting, surface deformation and earthquake focal mechanism studies suggest movements on north- and northeast-trending structures. The main shock, the aftershocks, surface faulting and changes in InSAR-derived surface elevation all occur in a region bounded to the south by a prominent northwest-trending fault and to the north by a west-northwest-trending domain-bounding structure. Thus, we interpret the north-trending thrust fault associated with the main Lake Muir event as due to local stress concentration of the regional east–west stress field at the intersection of these structures. Further, we propose that a particularly large west-northwest-trending structure may be broadly focusing stress in the Lake Muir area. These findings encourage similar studies to be undertaken in other areas of Australia's southwest to further the current understanding of seismic release in the region. KEY POINTS: A large ML 5.7 earthquake occurred in southwest Western Australia in September 2018, damaging infrastructure and forming a 40 cm-high thrust fault scarp. An aeromagnetic interpretation of the Lake Muir region revealed that the new scarp aligned with pre-existing faults that were reactivated. Local and regional structures likely acted as regional stress focusers in the Lake Muir area. Identifying regional stress-focusing structures is important for the purpose of understanding seismic risk in intraplate areas such as Western Australia.